Caracterização de águas produzidas provenientes de plataformas marítimas da bacia do Ceará - Braz, Ana Kátia de Sousa (2014)
In this study, we characterized 238 samples of water produced from four different production fields, all from offshore fields of the Ceará basin, called The field of production, production field B, C production and field production field D. were determined anions (acetate, chloride, formate, sulfate) using ion chromatography; except for the bicarbonate anion was determined using potentiometric titration. And, cations (Barium, Calcium, Strontium, total iron, lithium, magnesium, potassium, sodium) using the optical emission spectrometry with inductively coupled plasma. For statistical analysis, we used as a tool, the PCA (principal component analysis) and HCA (hierarchical cluster analysis). In evaluating the quality of the data, we used the ionic balance. To visualize the results, we used the box plot graph where one can observe that the production field, followed by the production field B, are prone to corrosion and fouling, respectively. As well, the D production field that showed propensity to corrosion, but on a smaller scale. It is worth stressing the need for individual characterization of the samples, to knowledge of the main existing constituents. For these constituents can incur high costs in maintaining the productive process of the oil industry; due to corrosion pitting type, which promotes change the look and structure of stainless steel, widely used in the oil industry; and incrustations which tend to deposit on the walls of pipes, which may cause problems such as pressure loss, decreased production flow and an increase in power consumption.